Perceval or Trifecta to Prevent Patient–Prosthesis Mismatch - Daniel Hernandez-Vaquero (Journal of Clinical Medicine, 2020)
The Trifecta aortic valve has excellent hemodynamics characteristics. Moreover, the Perceval prosthesis may achieve better hemodynamics than the conventional valves; therefore, it has been proposed to reduce the incidence of patient–prosthesis mismatch. Our aim was to compare the prevalence of this complication between both prostheses. All patients who underwent valve replacement with a Perceval or a Trifecta from 2016 to 2020 at our institution were included. We calculated the prevalence of patient–prosthesis mismatch for each prosthesis and size and performed a multinomial logistic regression model to investigate the impact of choosing one prosthesis over the other. A total of 516 patients were analyzed. Moderate mismatch was present in 33 (8.6%) in the Trifecta group and 28 (21.4%) in the Perceval group, p < 0.001. Severe mismatch was present in 8 (2.1%) patients with Trifecta and 5 (3.8%) patients with Perceval, p = 0.33. Compared with the Perceval, the Trifecta prosthesis was shown to reduce moderate patient–prosthesis mismatch: OR = 0.5 (95% CI 0.3–0.9, p = 0.02). Both prostheses led to a similar risk of severe patient–prosthesis mismatch: OR = 0.9 (95% CI 0.3–2.8, p = 0.79). Both prostheses provide a very low risk of severe patient–prosthesis mismatch. Compared with the Perceval prothesis, the Trifecta prosthesis is able to reduce by 50% the risk of moderate mismatch.